Q: How do you simplify n minus 10 plus 9n minus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

n-10+(9n-3)=10n-13

If it is: 13m+5n-6m+9n Then simplified it is: 7m+14n

9n + n = 10n

11m + 6n - 2m + 9n = 9m + 15n or 3(3m + 5n)

You need to get n alone.9n=45 → Divide by 9n=45/9n=5

Related questions

n - 10 + 9n - 3 = 10n - 13

15m + 4n - 5m + 9n = 10m + 13n

Add them together. They equal 2n.

8m + (4n - 6m) + 9n =8m + 4n - 6m + 9n =(8m - 6m) + (4n + 9n) =2m + 13n

n-10+(9n-3)=10n-13

The equation N-10 plus 9N-e equals 10N-3. This is a math problem.

Solve 5n+4n+32: Simplify the expression. 4n+5n+32=0; 9n+32=0 Group all constants on the right side of the equation. 9n+32=0; 9n+32-32=0-32; 9n=0-32; 9n=-32 Isolate the n. 9n=-32; 9n/9=-32/9; n=-32/9

-5 plus 9n plus 6 is 1 plus 9n.

If it is: 13m+5n-6m+9n Then simplified it is: 7m+14n

-26

9n + n = 10n

it equals -15